2018
DOI: 10.1103/physrevb.98.014437
|View full text |Cite
|
Sign up to set email alerts
|

Apparent ferromagnetism in the pinwheel artificial spin ice

Abstract: Magnetic artificial spin ice provides examples of how competing interactions between magnetic nanoelements can lead to a range of fascinating and unusual phenomena. We examine theoretically a class of spin ice tilings, called pinwheel, for which near degeneracy of spin configuration energies can be achieved. The pinwheel tiling is a simple but crucial variant on the square ice geometry, in which each nanoelement of square ice is rotated some angle about its midpoint. Surprisingly, this rotation leads to an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 23 publications
5
62
0
Order By: Relevance
“…In particular, Morrison et al 21 pointed out the importance of vertex of interactions and their dependence on geometry. A simply modified square ASI system provides a recent example of emergent dynamics: the 'pinwheel' ice 22,23 . The pinwheel geometry is obtained by rotating each island in square ASI around its centre 23 .…”
mentioning
confidence: 99%
“…In particular, Morrison et al 21 pointed out the importance of vertex of interactions and their dependence on geometry. A simply modified square ASI system provides a recent example of emergent dynamics: the 'pinwheel' ice 22,23 . The pinwheel geometry is obtained by rotating each island in square ASI around its centre 23 .…”
mentioning
confidence: 99%
“…The effects of open boundaries on nanomagnetic arrays have also been discussed by Macêdo et al 38 for the pinwheel artificial spin ice, where it was shown that for OBC the ground state is composed by domains that are not present in the system with PBC. In addition, they found that different domain structures appear depending on the lattice shape and edge types.…”
Section: Open Boundary Conditionsmentioning
confidence: 87%
“…8 The square ASI geometry has an antiferromagnetic (AFM) ground state (GS) ordering, where each set of four islands is formed by two orthogonal pairs of collinear Ising spins lying in a plane, with one pair aligned head-to-head and the other pair tail-to-tail. 1 In square ASI, the GS is well defined, 9 with the higher energy states separated significantly in energy, 1,10 and field-driven reversal occurs through sequential chain flipping 11,12 also referred to as Dirac strings. The recently reported 'pinwheel' geometry 10,[13][14][15] is created by rotating each island in a square lattice about its centre by 45 o (c.f.…”
Section: Introductionmentioning
confidence: 99%
“…As the island rotation angle is increased from 0 to 45 o , the dominant nearest-neighbour (NN) coupling in square ASI decreases in favour of an increased coupling to more distant islands. 10 In a small range of rotation angles around 45 o , the energy level spacings are significantly reduced, creating a near-degenerate system with two-dimensional (2-D) superferromagnetic 16 GS ordering. 10 The transition between square and pinwheel ice has been mapped as a function of rotation angle, yielding insight into defect formation and the demonstration of a true ice manifold in a 2-D system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation